(untitled) (Academia Science Repository, 2023)
Under the heading "Cerebrovascular diseases" there are diseases similar in clinical and pathogenetic characteristics to DE: I67.2 - cerebral atherosclerosis, I67.3 - progressive vascular leukoencephalopathy (Binswanger’s disease), I67.4 - hypertensive encephalopathy, I67.8 - cerebral ischemia (chronic). Unfortunately, the real prevalence and incidence of DE in our country is still unknown. The term cerebrovascular disease, which came to us from abroad (from the English cerebrovascular disease) is not entirely successful, because. in the domestic neurological school, it is customary to name diseases in a pathogenetic sequence. Undoubtedly, the term cerebrovascular disease is more logical, emphasizing the primary role of vascular pathology and hemodynamic disturbances, which subsequently leads to acute or chronic cerebral ischemia.